COVID-19 vaccine hesitancy and attitudes of subjects with disability and their carers in Saudi Arabia: a cross-sectional study - Sayed, Anwar A. (Frontiers in Public Health, 2024)
The COVID-19 pandemic has caused significant disruption to countries worldwide, including Saudi Arabia. The fast preventative measures and the mass vaccine enrollment were vital to contain the pandemic in the country. However, vaccine hesitancy was a significant obstacle to taking the vaccine but was not previously explored. One hundred eighty-six subjects with disabilities were enrolled in this study in an attempt to explore their hesitancy and attitudes toward COVID-19 vaccines. Most participants were previously diagnosed with COVID-19 and had a close family who was also diagnosed with it. Most of them were willing to be vaccinated but had not received previous vaccinations. Official sources of information, e.g., TV/radio, were an essential factor driving their intention to get vaccinated. Beliefs that drove participants' vaccine acceptance include vaccine safety, sufficient testing before its release, and its ability to protect from infection. The results of this seminal study provide insights to public health policymakers, which should be considered and taken together in light of other studies addressing the population's vaccine hesitancy.